2020
DOI: 10.1016/j.bbr.2019.112333
|View full text |Cite
|
Sign up to set email alerts
|

Reward and immune responses in adolescent females following experimental traumatic brain injury

Abstract: The pathology of traumatic brain injury (TBI) adversely affects many brain regions, often resulting in the development of comorbid psychiatric disorders including substance use disorders (SUD). Although traditionally thought to be an epidemic that predominantly affects males, recent clinical studies report females have higher rates of concussions and longer recovery times than males. Yet, how neurotrauma, particularly deep within the brain, between the sexes is differentially manifested remains largely unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The influence of biological sex after TBI is epitomized by the observation that males and females have different rates of post-traumatic drug and alcohol disorders [4,84,85]. Consistent with these clinical data, males and females perform differently in CPP after TBI [31,32,86]. Females are more susceptible to addiction and drug-related effects than males [87], both in humans [88,89] and in rodent models [90,91].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The influence of biological sex after TBI is epitomized by the observation that males and females have different rates of post-traumatic drug and alcohol disorders [4,84,85]. Consistent with these clinical data, males and females perform differently in CPP after TBI [31,32,86]. Females are more susceptible to addiction and drug-related effects than males [87], both in humans [88,89] and in rodent models [90,91].…”
Section: Discussionmentioning
confidence: 82%
“…Importantly, TBI alters drug-induced CPP [28,29]. Sex differences in CPP, including after TBI, have also been identified [30][31][32]. Thus, it is important to describe both biological sex-and TBI-related effects on dopaminergic circuitry in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…In an adult mouse study using CCI, resident microglia are increased 7 days post-injury in the cortex [7]. Similarly, adult mouse CCI shows increases in microglia on the ipsilateral side of the brain at 2-and 14-days post-injury with parallel increases in PSD95 + immature microglia at 2 days, suggesting a de novo birth and maturation of resident microglia [17]. Using Marmarou's weight drop model, Balb/c mice show macrophage increases at 1-, 2-, and 3-days post-injury, whereas microglia in the brain dramatically decrease [8].…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, the experience of TBI has been shown to be both an outcome and predictor of disordered substance use (Graham & Cardon, 2008; West, 2011). Recent studies have shown TBI status appears to sensitize reward processing to cocaine in rodents (Cannella et al, 2019), as well as alter neural systems related to reward in people who experienced a TBI early in life, which may contribute to disordered substance use (Cannella et al, 20199). Specific to cannabis, TBI status may influence motivations to use cannabis; one study found that individuals with at least moderate-to-severe TBI reported using cannabis after their TBI, in part, as a way to cope with ongoing stress or anxiety (Hawley et al, 2018).…”
Section: Discussionmentioning
confidence: 99%